Defining Health Mavens On Demographic Characteristics: A Pilot Study In Istanbul - Cengiz, Emrah; Akyuz, Irfan; Omay, Gultuvin Gur; Bosat, Merve (European Scientific Journal, ESJ, 2016)
Market mavens are people who have general information about the market and share this information with other consumers even though they do not use the product or service. Market mavens are consumers who actively communicate with the market and every level of the product life cycle. In this study, it is aimed to define the demographic characteristics of health mavens who are a special type of market mavens. In the scope of the study, consumers that are aged 18 and above are included. 387 questionnaire forms are evaluated. People participated in the study are %52,4 female, %47,6 male; %49,8 single, %50,2 married and %35,9 18-28 aged, %26,1 29-39 aged, %22 40-50 aged and %16 51 and above. Employed people form %78,6, students %13,1, unemployed %8,3 of the sample. Lower income group %22,2, middle income group %60,5 and high income group %17,3 are classified on monthly basis. Besides, 387 people of the sample are high level %48,5, middle level %25,1 and low level %26,4 are health mavens. According to the correlation analysis, age, education and marital status are determining characteristics of health mavens. But, there is no meaningful relationship between gender, occupation and income levels of participants’ health maven levels statistically.